A Systematic Approach to Improving the Performance of Spiral Antenna - Hidayat, Rahmad; Rushendra, Rushendra; Agustina, Ellisa; Wulandari, Ike Yuni; Rahim, Robbi (Jurnal Telematika, 2017)
Implementation of antennas in various areas of wireless technology, became one of the main drivers of the advancement of wireless digital communications technology today. They are applicable to mobile communications, microwaves, Wireless Fidelity, satellites for various needs such as commercial, military, health, education, telemetry and much more. Then, the frequency independent antenna has become a major driver of intensive research and development of spiral antennas in generating large bandwidth. In this paper, a new approach will be adopted that will identify and analyze the wideband spiral antenna design with its various properties and look for opportunities for the application of various forms of novel advanced spiral antennas with improved performance. The results of identification and analysis increasingly show that the improvement of spiral antenna performance is highly dependent on design optimization; and continuous assessment of how techniques, methods, and experiments are possible for the performance improvement of existing spiral antenna properties. These performance improvements are in bandwidth, gain, voltage standing wave ratio (VSWR), polarization, improved radiation patterns that can be seen from the desired transmit direction diagram.Penerapan antena di berbagai bidang teknologi wireless, menjadi salah satu penggerak utama kemajuan teknologi komunikasi digital wireless saat ini. Penerapan tersebut terdapat baik pada komunikasi seluler, gelombang mikro, WiFi, satelit untuk berbagai kebutuhan seperti komersial, militer,  kesehatan, pendidikan, telemetri dan masih banyak lagi lainnya. Kemudian antena frekuensi bebas telah menjadi pendorong utama penelitian intensif dan pengembangan antena spiral dalam menghasilkan bandwidth yang besar. Dalam tulisan ini, pendekatan baru akan diadopsi yang akan mengidentifikasi dan menganalisis desain antena spiral wideband dengan berbagai sifatnya dan mencari peluang untuk penerapan berbagai bentuk antena spiral baru yang canggih dengan kinerja yang lebih baik. Hasil identifikasi dan analisis semakin menunjukkan bahwa peningkatan kinerja antena spiral sangat bergantung pada optimalisasi desain; dan penilaian terus menerus tentang bagaimana teknik, metode, dan eksperimen yang memungkinkan untuk peningkatan kinerja antena antena spiral yang ada baik dalam bentuk Archimedean, square, star, hexagonal, sinuous, equiangular, dan lainya. Peningkatan kinerja tersebut ada pada bandwidth, gain, voltage standing wave ratio (VSWR), polarisasi, pola radiasi yang semakin membaik yang dapat terlihat dari diagram arah pancar yang diinginkan.